2011
DOI: 10.3349/ymj.2011.52.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Procalcitonin as an Early Diagnostic Marker of Bacteremia in Patients with Acute Fever

Abstract: PurposeProcalcitonin (PCT) is a current, frequently used marker for severe bacterial infection. The aim of this study was to assess the ability of PCT levels to differentiate bacteremic from nonbacteremic patients with fever. We assessed whether PCT level could be used to accurately rule out a diagnosis of bacteremia.Materials and MethodsSerum samples and blood culture were obtained from patients with fever between August 2008 and April 2009. PCT was analyzed using a VIDAS® B.R.A.H.M.S PCT assay. We reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 21 publications
13
35
0
3
Order By: Relevance
“…In the current study, pre-op values of PCT were measured below 0.5 ng/ml. Kim et al demonstrated that a cut-off PCT concentration of 0.4 ng/ml was able to rule out bacteremia in patients with acute fever [7]. In the present study, the average post-op PCT levels for both groups of patients were higher than the normal interval.…”
Section: Discussionsupporting
confidence: 51%
“…In the current study, pre-op values of PCT were measured below 0.5 ng/ml. Kim et al demonstrated that a cut-off PCT concentration of 0.4 ng/ml was able to rule out bacteremia in patients with acute fever [7]. In the present study, the average post-op PCT levels for both groups of patients were higher than the normal interval.…”
Section: Discussionsupporting
confidence: 51%
“…10 In addition, Kim et al have reported that when PCT cut-off concentrations of 0.05-5.98 ng/mL were used, the PPVs were 14.0-48.0% and NPVs were 94.0-99.0%. 16 These two studies and two additional reports indicate that the PPV at which the PCT concentrations indicate bacteraemia is generally about 50%, although this will differ depending on the cut-off concentration, the patient group, and the hospital. 9,11,16,17 In a recent meta-analysis of studies on bacteraemia markers, Jones et al reported only moderate diagnostic performance for PCT as a single test for diagnosing bacteraemia in emergency department patients, demonstrating a sensitivity of 76% and a specificity of 73% at a cut-off concentration of 0.4-0.5 ng/mL.…”
Section: Discussionmentioning
confidence: 93%
“…Infection characterizes the presence of an inflammatory response and tissue injury as a result of host interaction with multiplying bacteria [11]. The early recognition of infection is paramount in the management of diabetic foot disease, thus a rapid and reliable test to rule out bacterial infection would be helpful in decision making [14].…”
Section: Introductionmentioning
confidence: 99%